FORMATION OF PROJECT COMPETENCE FOR FUTURE PROFESSIONALS OF CREATIVE SPECIALITIES - HAPON-BAIDA, Liudmyla; DERKACH, Tetiana (Physical and Mathematical Education, 2024)
Problem statement. The formation of project competence among students of the educational and professional program "Graphic Design" was investigated in experimental training, during which students studied and mastered design project elements. Materials and methods. The research was conducted at the Institute of Computer and Information Technologies and Design, with the participation of second-year students in specialty 022 Design ("Graphic Design"). Experimental learning has been integrated into the current educational process in the "Design and Projection" discipline. It consisted of lectures and practical classes and was focused on implementing the projects "Development of a personal sign/logo" and "Development of a printed edition logo." Mastery of each design element was determined by evaluating program results for each component and lesson. Studying according to the project method of students of creative specialties contributed to combining scientific, innovative, and technological elements in students’ creative projects. That activity did facilitate project competence. Results. During the formative experiment, the respondents demonstrated mastery of various design project elements at 80-92%, in contrast to the ascertainment stage, where the mastery was 22.9-70.7%. The scores for the elements of long-term research (LT), reflection/thoughtfulness (RT), and critique/review (CR) increased by 47-63.3%, and for the elements of complex problem/question (CQ), authenticity/reality (AR), student voice (SV), and public product (PP) by 10-36%. The success of mastering the design project elements depended on using special methods of forming them and the number of classes devoted to them. The same number of classes differently influenced SP, TD, AS, CP, and PP, ranging from 80%-90.3%. The CR element’s perception level is significantly lower (80%), which depends on the formation methods and the number of assigned classes. Conclusions. The author’s methodology of project competence forming among students of the educational and professional program "Graphic Design" based on a design project has proven successful and can be recommended for implementation. We focus further research on mastering the Critique/Review element by students of those specialties.